Growth Rate of (Oreochromis sp) Saline Tilapia Seeds Cultured in Biofloc System using Fermented Vegetable Waste Feed - Aldi, Arifaldianzah; Khaeriyah, Andi; Anwar, Asni; ., Burhanuddin; Salam, Nur Insana; Saleh, Muhammad Syaiful (Hasanuddin University, 2022)
This study aims to determine the growth rate of Salin tilapia (Oreochromis sp.) which is cultivated in a biofloc system using fermented vegetable waste feed. The experimental design used was a completely randomized design (CRD) with 4 treatments and 3 replications and the feed used was fermented vegetable waste with different doses of prebiotics, treatment A Control, B 30 ml/kg, C 40 ml/kg, and D 50 ml /kg. The results showed that the feeding of fermented vegetable waste had a significantly different effect (P<0.05) on the growth rate. Fermented vegetable waste feed with a probiotic dose of 30ml/kg showed a daily growth of 5.44% although the survival from the ANOVA test results showed no significant difference.